Diminished Global Arginine Bioavailability and Increased Arginine Catabolism as Metabolic Profile of Increased Cardiovascular Risk - Tang, W.H. Wilson; Wang, Zeneng; Cho, Leslie; Brennan, Danielle M.; Hazen, Stanley L. (Journal of the American College of Cardiology, 2009)
We hypothesized that an integrated assessment of arginine with its catabolic products might better predict cardiovascular risks than arginine levels alone. Arginine is the sole nitrogen source for nitric oxide (NO) synthesis. The major catabolic products of arginine are ornithine and citrulline. Plasma levels of free arginine, ornithine, citrulline, and the endogenous NO synthase inhibitor asymmetric dimethylarginine (ADMA) were measured with liquid chromatography coupled with tandem mass spectrometry. We examined the relationship of global arginine bioavailability ratio (GABR) (defined as arginine/[ornithine + citrulline]) versus arginine and its catabolic metabolites to prevalence of significantly obstructive coronary artery disease (CAD) and incidence of major adverse cardiovascular events (MACE) (death, myocardial infarction, stroke) over a 3-year follow-up in 1,010 subjects undergoing elective cardiac catheterization. Patients with significantly obstructive CAD had significantly lower GABR (median [interquartile range]: 1.06 [0.75 to 1.31] vs. 1.27 [0.96 to 1.73], p < 0.001) and arginine levels [mean: 68 ± 20 μmol/l vs. 74 ± 24 μmol/l, p < 0.001) than those without significantly obstructive CAD. After adjusting for Framingham risk score, C-reactive protein, and renal function, lower GABR (but not arginine levels) and higher citrulline levels remained significantly associated with both the prevalence of significantly obstructive CAD (adjusted odds ratio: 3.93, p < 0.001, and 5.98, p < 0.001, respectively) and 3-year risk for the incidence of MACE (adjusted hazard ratio: 1.98, p = 0.025, and 2.40, p = 0.01, respectively) and remained significant after adjusting for ADMA. GABR might serve as a more comprehensive concept of reduced NO synthetic capacity compared with systemic arginine levels. Diminished GABR and high citrulline levels are associated with both development of significantly obstructive atherosclerotic CAD and heightened long-term risk for MACE.